TATA CARA PEMUNGUTAN PAJAK PENERANGAN JALAN PADA KANTOR BAPPENDA KABUPATEN KOTAWARING TIMUR - Dias Tri Utami; Saipudin; Suyatno (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
This final project aims to discuss the procedures for collecting PPJ at the Bappenda Office of East Kotawaring Regency.The results obtained from this study are that the PPJ collection procedure is carried out based on Government Regulation Number 91 of 2010. The effectiveness of PPJ in Kotawaringin Timur Regency in 2018-2020 is in the effective category, but efforts are still needed to be made so that PPJ continues to increase and can make a good contribution to the region. The Bappenda Office of East Kotawaringin Regency must also move to provide socialization, education, improve and facilitate services to the community in carrying out their tax obligations.